Rehabilitation of disturbed tropical land with trickle irrigation for agricultural production. - Said, Salim (1989)
There are about 200,000 hectares of tin tailings in Malaysia laid waste by the mining operations. Being mostly sandy, the total available moisture is only 8.3% by volume. A water balance study is conducted to determine the fraction of trickle irrigation water consumed by a crop-green spinach (Amaranthus tricolor).